PENERAPAN PROTOKOL PENANGANAN DIABETES MELLITUS PADA PASIEN GERIATRI DI PANTI WREDHA DHARMA BAKTI KASIH SURAKARTA - Deoni Vioneery; Noor Fitriyani; Martini Listrikawati; Mutiara Dewi Listiyanawati; Dirhan Dirhan (MEDIKA TRADA, 2025)
Diabetes mellitus (DM) is one of the chronic diseases that often occurs in the elderly population, especially in nursing homes. The management of DM in geriatric patients requires a special approach that takes into account their physical, psychological, and social conditions. This study aims to analyze the implementation of the DM management protocol for geriatric patients at the Wonogiri Nursing Home and to identify its impact on blood sugar control and patients' quality of life. The study employed a quantitative research method with a pre-experimental design, involving 30 geriatric patients diagnosed with DM. Data were collected through direct observation using the Diabetes Quality of Life (DQOL) questionnaire. The results of the study using the non-parametric Wilcoxon Signed-Rank Test showed that before the protocol was implemented, 23 people (60.52%) had been diagnosed with DM and required monitoring and further management, while 15 participants (39.48%) were in the pre-diabetes category) and after implementation (31 participants (81.58%) showed improvement toward the pre-diabetes category, while 7 participants (18.42%) remained in the controlled DM category). The Z-score result of -4.879 with p = 0.000 (p < 0.05) indicates a statistically significant improvement in diabetes status before and after the implementation of the management protocol, and contributes to the control of diabetes complications among the geriatric population at the Panti Dharma Bakti Kasih Surakarta. Keywords: diabetes mellitus, geriatrics, management protocol